Sistem Pakar Diagnosa Awal Penyakit Ginjal Berbasis Web Menggunakan PHP DAN MYSQL - Buhori Muslim; Yadi; Madi Harta (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
The design of expert systems for diagnosis of kidney disease is to build an expert system to diagnose kidney disease that provides information on diseases of the kidney through diagnosis of symptoms felt by sufferers with Web-based programming. Currently, if people want to diagnose with doctors to hospital or other health centers and have to wait their turn or queue to consult with doctors, to facilitate the consultation process needs a system that allows people to consult quickly, precisely and accurately. In designing this system using PHP and mysql programming language. The type of data collection obtained from the place of research, interviews with an expert, books and other literature. The method used in system development is Extreme Programming method which consists of Planning, Design, Coding, Test and Release. And the results of this design is to produce a system that provides information about kidney disease and help diagnose the disease through symptoms experienced.